STRATEGI DAN TANTANGAN PENGEMBANGAN HOTEL SYARIAH DI KOTA PAYAKUMBUH - Nedi, Laras Annisa Ulfitri (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2023)
One of the potential tourist destinations in West Sumatra Province is Payakumbuh, Payakumbuh has a good positioning in preparing for the arrival of tourists from Muslim countries and regions because Islamic culture has been well ingrained and integrated with the philosophy of life of the traditional minang people, adat basandi sarak, sarak basandi kitabullah. In order for halal tourism in Payakumbuh to grow, supporting components such as sharia hotels need to be developed. This study aims to explore and describe the potential of sharia hotels in Payakumbuh, and propose development strategy by exploring this potential. This study uses qualitative method to define problems and present sharia hotel development strategies. With the repeal of Permenparekraf number 2 of 2014, there is lack of legislation, especially related to sharia hotel regulations, so an active role of the government is needed in socializing the concept of sharia hotels by providing training, education and technical guidance to local government officials, hoteliers, communities and related parties through workshops, professional education/training, focus group discussions and mock studies as well as required commitment from business actors in implementing the principles of sharia hotel management in accordance with the Fatwa of the National Sharia Council of the Indonesian Ulama Council (DSN-MUI) Number 108/DSN-MU/X/2016, so that Muslim tourists receive protection from the halal aspects of products, services and hotel business management. With good quality and standardized sharia-based hotel services, a good hotel brand image will be created for Muslim tourists and will create a revisit intention.